IMPLEMENTASI PENDIDIKAN KEBENCANAAN DALAM MEMBENTUK DESA TANGGUH BENCANA BERBASIS PEMBERDAYAAN PELAJAR DAN MASYARAKAT DI DESA BESOLE KABUPATEN TULUNGAGUNG - Khusna, Nur Isroatul; Samudra, Bayu (Journal of Education and Learning Sciences, 2022)
Besole village is one of the villages in Tulungagung Regency which is near the center of the world's active plate collision and is directly adjacent to the Ocean. The influence of this location makes this village rich in minerals, namely as the number one largest marble producer in Indonesia. But behind that, this village has a big threat from natural disasters. This is evident over the years that this area has been hit by floods and landslides and has a threat of a tsunami. Therefore, an effort to empower the community is needed to form a disaster-resilient village through the implementation of disaster mitigation management education. This program is intended for students and the community due to their vulnerability to being affected by disasters. The purpose of this activity is to 1) determine the planning of disaster mitigation management education implementation programs 2) carry out several activities in disaster-based community empowerment efforts, 3) increase knowledge, skills and attitudes of disaster preparedness, 4) find out the advantages, disadvantages, supporters and obstacles of empowerment programs disaster-based society. This study uses a research-based Participatory Action Research (PAR) method which is divided into stages of planning, action, observation and reflection. The results of this study are 1) the planning stage is held to formulate various actions based on the results of preliminary research, focus group discussion and disaster mitigation guidance, 2) the action stage contains various activities, namely waste management on the coast, implementation of earthquake and tsunami learning simulation models at the elementary and junior high school levels, installation of evacuation route signs in several vital objects, use of biopore infiltration hole technology, counseling on organic and inorganic waste management through waste banks. , making a map of the disaster evacuation route for the coastal area of ​​Besole Village, 3) this activity contributes to the Besole village community in increasing knowledge, skills and attitudes of disaster preparedness, 4) the advantages and supporters of this activity, the most important of which is the support from various parties, both from the government and non-government, while the first factor that becomes a shortage and obstacle is the location factor which is difficult to access.